Characterizations of Outer Generalized Inverses. Issue 4 (1st December 2017) - Wang, Long; Castro-Gonzalez, Nieves; Chen, Jianlong
Abstract: Let R be a ring and b, cR . In this paper, we give some characterizations of the (b, c) -inverse in terms of the direct sum decomposition, the annihilator, and the invertible elements. Moreover, elements with equal (b, c) -idempotents related to their (b, c) -inverses are characterized, and the reverse order rule for the (b, c) -inverse is considered.